CONSISTENCY OF WITNESSES IN NOTARY OFFICIAL AND PPAT - NUGROHO, MUKHANET WAHYU; HARTIWININGSIH; ISHARYANTO (Innovare Journal of Social Sciences, 2023)
In making an Akta Autentik (Authentic Official) made by a Notary and a Land Official Making Officer or what is called a PPAT which is the authority, it consists of several parts and one of the things that must be in the Authentic Official section is a witness, which is defined as an identifier witness and an instrumenter witness. Instrumenter witness is a mandatory thing with a minimum number of two people who must have the status as employees in the related PPAT Notary Office, their important existence makes many considerations that must be taken if they have to replace one or both of them, including when the PPAT Notary cooperates with freelancers who require it become an instrumenter witness, but often the PPAT Notary does not know the legal actions and the actual identity in the draft official, he receives from the freelancer which creates a gap to create a dispute, besides that, another loss received by the Notary and PPAT is that his credibility is starting to be doubted. This study aims to find out what and what effect it has on the consistency of instrumenter witnesses in an Authentic Official, this study uses a normative juridical research method by comparing das sein and das sollen about instrumenter witnesses in an Authentic Official, in which the results of research on the consistency of complementary witnesses can lead to a a dispute because the PPAT Notary in making or signing the official does not meet directly with the interested parties which can injure the making and meaning of the Authentic Official definition and is at high risk for the Notary and the PPAT itself. Therefore, with this writing, it is expected that Notaries and PPATs who have been or are new and will be actively serving to be able to be careful in carrying out their duties and positions, especially in the inclusion of witnesses in the official, including to cooperate with freelancers.